Chicken soup for the soul: teens talk getting into college: 101 true stories from kids who have lived through it (New York : Chicken Soup for the Soul Publishing, 2008)
Literary collections.
Keywords: College applications-United States -- Anecdotes; Teenagers - Conduct of life -- Anecdotes; Teenagers -- Literary collections